Pengaruh Struktur Kepemilikan Keluarga Terhadap Kinerja Perusahaan Pada Sektor Perdagangan, Jasa, dan Investasi - Stephanie Natalie Tanzil; Juniarti Juniarti Juniarti (Business Accounting Review, 2017)
This study aimes to examine and to prove the influence of family ownership structure on firm performance by using ROA. This study also used control variables of GCG score and intensity of competition. The research was conducted on sector trading, service, and investment companies within 2010-2015 with the samples of 480 observations and measured by using SPSS software. The result showed that family ownership structure had significant negative affect on firm performance. In addition, the control variables of GCG score and intensity of competition had significant positive affect on firm performance.